2017
DOI: 10.1371/journal.pone.0183020
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study comparing lateral and diagonal maximum weight shift in people with stroke and healthy controls and the correlation with balance, gait and fear of falling

Abstract: Impaired balance is common post stroke and can be assessed by means of force-platforms measuring center of pressure (COP) displacements during static standing, or more dynamically during lateral maximum weight shift (MWS). However, activities of daily life also include diagonal MWS and since force platforms are nowadays commercially available, investigating lateral and diagonal MWS in a clinical setting might be feasible and clinically relevant. We investigated lateral and diagonal MWS while standing in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…This instrument has been shown to have high reliability, with a testretest intraclass coefficient (ICC) of 0.83. 24…”
Section: Static and Dynamic Balance Abilitymentioning
confidence: 99%
“…This instrument has been shown to have high reliability, with a testretest intraclass coefficient (ICC) of 0.83. 24…”
Section: Static and Dynamic Balance Abilitymentioning
confidence: 99%
“…The CoP, which is another informational element for postural control, is often used as much as the GRF. We can judge a person’s state for stability with the location and velocity of the CoP [11,12]. We can also predict the gait speed of a person with the forward velocity of the CoP in the midfoot [13] and get the user intention understanding of exoskeleton for controlling a robot system [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Biswas et al have shown that the characteristics of COP can enhance the predictive power to a constructed index for dynamic stability [ 12 ]. In other studies, COP measures were also used to assess postural stability among stroke patients [ 13 ], patients with post-stroke hemiparesis [ 14 ] and patients with rheumatic disease [ 15 ]. In a recent study, Johansson et al investigated how the COP sway can be used to predict future falls.…”
Section: Introductionmentioning
confidence: 99%